Renewable diesel via hydrothermal liquefaction of oleaginous yeast and residual lignin from bioconversion of corn stover - Collett, James R.; Billing, Justin M.; Meyer, Pimphan A.; Schmidt, Andrew J.; Remington, A. Brook; Hawley, Erik R.; Hofstad, Beth A.; Panisko, Ellen A.; Dai, Ziyu; Hart, Todd R.; Santosa, Daniel M.; Magnuson, Jon K.; et al. (Applied energy, 2019)
[Display omitted] •Continuous hydrothermal liquefaction of oleaginous yeast and lignin drives efficientcarbon utilization from corn stover.•A high quality distillate blendstock ideal for diesel, jet, and marine fuel applications was produced by continuous-flow biocrude hydrotreating.•Techno-economic analysis suggests a doubling of renewable distillate fuel output compared to contemporary biorefinery designs. Oleaginous yeast can produce high yields of lipids from hydrolyzed lignocellulosic carbohydrates, but the difficulty and cost of extracting the lipids from the bioreactor broth, as well as the lack of profitable options for valorizing feedstock lignin are major barriers to cost-competitive production of renewable diesel from corn stover via bioconversion. Hydrothermal liquefaction of lignocellulosic biomass effectively breaks down and converts lignin into biocrude oil products, but provides relatively low yields of biocrude from feedstock carbohydrates. In the present study, bioconversion and hydrothermal liquefaction were integrated in a new hybrid approach that combines the advantages of both processes to produce a high quality distillate fuel blendstock. Eight bioreactor cultures of the oleaginous yeast Lipomyces starkeyi were grown in pretreated corn stover hydrolysate or simulated hydrolysate media, with dry cell mass yields from sugar of up to 0.43 g/g, and yields of intracellular triglyceride lipids from sugar (measured as fatty acid methyl esters) of up to 0.26 g/g. The lipid-rich cell mass in the bioreactor broth was pooled and mixed with pretreated corn stover lignin to produce a slurry intermediate with a total mass of 23.5 kg. The slurry was fed to a continuous hydrothermal liquefaction reactor at a dry solids loading of 16.3% to produce biocrude oil with a carbon yield of 55% and a mass yield of 40% from the feedstock. The biocrude was then hydrotreated to produce a renewable hydrocarbon fuel blendstock, with the majority of the product boiling in the distillate range. Techno-economic analysis suggested that a biorefinery employing this integrated, hybrid conversion approach could produce approximately twice as much distillate fuel blendstock than contemporary biorefinery designs that rely solely on lipids solvent-extracted from oleaginous yeast for production of distillate blendstocks from corn stover hydrolysate. Sensitivity analysis of the proposed biorefinery design suggested that the cost of production could be reduced to $3/gasoline gallon equivalent or less by addressing identified research gaps, such as optimizing the separation of biocrude to recover additional hydrocarbon from the aqueous phase of the reactor effluent. Our results provide a proof-of-concept for a new hybrid biorefinery design that could enhance domestic production of renewable diesel, jet, and marine fuel from corn stover or other forms of lignocellulosic biomass.